STUDYING THE CHARACTERISTICS OF A NEW COMPOSITE FABRIC FOR WORKWEAR - M.K. Rasulova; SH.L. Mamasolieva (International Journal of Innovations in Engineering Research and Technology, 2021)
The article is devoted to the creation of a new range of special-purpose fabrics with improved hygienic properties. The developed new composite fabrics belong to mixed inhomogeneous fabrics made of cotton thread, and for their intended purpose – clothing fabrics of special purpose.